2018
DOI: 10.1017/s0025315418000759
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of three sympatric species of stingrays on a tropical mudflat

Abstract: Periodic fish ingressions into intertidal areas during high tide are known to occur on tropical mudflats. This study aimed to elucidate the feeding ground function of coastal mudflats for three common stingray species in the Klang Strait, Malaysia. Stingrays (disc width range from 5.65–54.50 cm) sampled over 17 months using a large barrier net (~2 ha enclosure) at two sampling sites were examined for their diet composition, prey frequency and prey volume according to predator species and maturity. The index of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
3
5
0
Order By: Relevance
“…This indicates that F. margaritella acts as a small, low trophic level meso-predator that links benthos communities with top-predators in the Bijagós Archipelago. The presence of teleost items the stomach contents of F. margaritella suggests that the species occasionally consumes teleost prey, as observed in other batoid species ( Lim et al, 2019 ; Farias et al, 2006 ). Whereas other studies show that batoids ontogenetically include more teleost prey ( Gray, Mulligan & Hannah, 1997 ; Lim et al, 2019 ; Farias et al, 2006 ), in our study one YOY was observed to have consumed small teleost prey.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This indicates that F. margaritella acts as a small, low trophic level meso-predator that links benthos communities with top-predators in the Bijagós Archipelago. The presence of teleost items the stomach contents of F. margaritella suggests that the species occasionally consumes teleost prey, as observed in other batoid species ( Lim et al, 2019 ; Farias et al, 2006 ). Whereas other studies show that batoids ontogenetically include more teleost prey ( Gray, Mulligan & Hannah, 1997 ; Lim et al, 2019 ; Farias et al, 2006 ), in our study one YOY was observed to have consumed small teleost prey.…”
Section: Discussionsupporting
confidence: 55%
“…The presence of teleost items the stomach contents of F. margaritella suggests that the species occasionally consumes teleost prey, as observed in other batoid species ( Lim et al, 2019 ; Farias et al, 2006 ). Whereas other studies show that batoids ontogenetically include more teleost prey ( Gray, Mulligan & Hannah, 1997 ; Lim et al, 2019 ; Farias et al, 2006 ), in our study one YOY was observed to have consumed small teleost prey. The high proportion of unidentified prey encountered likely results from soft-bodied prey ( e.g ., polychaetes and small crustaceans) which may digest faster ( Farias et al, 2006 ).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…small bivalves and shrimp) (Gray et al, 1997). A similar ontogenetic shift was shown for other ray and benthic shark species (Bethea et al, 2007; Clements et al, 2022; Lim et al, 2018). Hollensead et al (2016) describes that juvenile smalltooth sawfishes ( Pristis pectinate , Pristidae) most likely use the edge of intertidal flats to ambush schools of mullet (Mugilidae) leaving the intertidal habitat during receding tide.…”
Section: Intertidal Habitat Use By Sharks and Rayssupporting
confidence: 76%